Socıal Competence, Human Capıtal and Entrepreneurıal Success (A Study on the Owner of Fish Trading Business) - Nurul Badriyah; Noermijati Noermijati (Department of Management, Faculty of Economics and Business, Brawijaya University, 2015)
It is undoubtful that entrepreneur need solid social competence and human capital to grow their busienss. With the case of Indonesia, most of the owners of fish trading business in Lamongan still market their fish in traditional market with the coverage of 40% of the area of East Java, 38% of Central Java and West Java, and the rest of 21% is outside Java. This trading sector has an open characteristics which means that there is no obstacle for those who want to join or leave the trading business and this condition requires trading businessmen to have more capabilities in terms of offering goods, searching for market opportunities, and maintaining a network of relations. This study aims to analyze whether social competence can act as a mediating variable between human capital and business success in the fish trading business owners in Lamongan. The process of data collection in this study was conducted on a population of 114 used to test the validity and reliability of 30 respondents, so that the sample 84 respondents were overall taken. The result of this study shows that human capital gives negative effect on business success while the social competence positively and significantly gives impact on the business success and has a perfect role as mediating variables in the relationship between human capital with business success. This study contributes to the development aspects of the study of the human resources stating that the better human capital an entrepreneur has, the better the social competence he has, and subsequently provides better opportunities to achieve business success.